Fundamentals of engineering thermodynamics - Moran, Michael J. (Wiley, 2008)
Fundamentals of Engineering Thermodynamics maintains its engaging, readable style while presenting a broader range of applications that motivate student understanding of core thermodynamics concepts. This leading text uses many relevant engineering-based situations to help students model and solve problems.